2001
DOI: 10.1038/sj.ijir.3900787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-blockers on sexual performance in men with coronary heart disease. A prospective, randomized and double blinded study

Abstract: In a prospective trial assessing the effects of beta-blockers on sexual function men with coronary heart disease were randomized to a 4 month treatment with sustained release metoprolol 95 mg or placebo. A standardized and validated self-report questionnaire (KEED ¼ Kö lner Erhebungsbogen der Erektilen Dysfunktion) dealing with several aspects of sexual performance in men had to be answered at the beginning and at the end of the study. Based on 65 patients completing the study, sex life seemed unaffected by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
6

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 17 publications
1
23
0
6
Order By: Relevance
“…16,32 Moreover, the KEED score, previously validated in the general population around Cologne, Germany, in the course of the Cologne Male Survey, was used as a control. 2,25 Results from both questionnaires correlated significantly in the present study population of patients with the metabolic syndrome. Thus, results are suggested to be valid and likely to be independent from incorrect response to the questionnaires.…”
Section: Methodology and Limitationsmentioning
confidence: 58%
See 1 more Smart Citation
“…16,32 Moreover, the KEED score, previously validated in the general population around Cologne, Germany, in the course of the Cologne Male Survey, was used as a control. 2,25 Results from both questionnaires correlated significantly in the present study population of patients with the metabolic syndrome. Thus, results are suggested to be valid and likely to be independent from incorrect response to the questionnaires.…”
Section: Methodology and Limitationsmentioning
confidence: 58%
“…These results are consistent with prior findings, which demonstrated a decrease in erectile function in patients treated with the calcium channel blocker nifedipine and the diuretic chlorthalidone, but not in patients who received b-receptor blockers. 20,[23][24][25][26] The adverse influence of treatment with statins on erectile function is somewhat surprising, taking into account the pleiotropic effects of statins, as for instance the improvement of endothelial function due to an upregulation of the endothelial nitric oxide synthase. 27,28 Recently the hydroxymethylglutaryl (HMG) coenzyme A reductase inhibitor rosuvastatin has been shown to exert beneficial effects on erectile function in diabetic mice.…”
Section: Cardiovascular Risk Factors and Erectile Dysfunctionmentioning
confidence: 99%
“…A prospective, randomized, double-blind study showed that patients' sex lives were unaffected by metoprolol treatment. 63 In another study, Wassertheil et al 6 demonstrated that the betaadrenergic blocker atenolol did not affect sexual function. In a study of 96 men with newly diagnosed cardiovascular disease and without ED, 31%…”
Section: Beta-adrenergic Receptor Blockersmentioning
confidence: 99%
“…Beta-blockers may cause SD depending on the degree of beta blockade. 41 Propranolol at high dose often causes ED, but lower doses of metoprolol, atenolol and carvedilol cause ED only as much as other antihypertensives. 42 Timolol eye drops have been reported to cause ED and may easily be overlooked as a causative agent.…”
Section: Effect Of Medications On Sexual Functionmentioning
confidence: 99%